2007
DOI: 10.1007/s10637-007-9039-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of amrubicin, 9-amino-anthracycline, in patients with advanced non-small-cell lung cancer: a West Japan Thoracic Oncology Group (WJTOG) study

Abstract: Amrubicin was an active, well-tolerated agent in the treatment of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Hematologic toxicity was found to be the principal toxicity of amrubicin monotherapy in previous phase II studies [14,15,16]. Likewise, the major adverse events in our study were hematologic toxicity, especially neutropenia and leukopenia.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Hematologic toxicity was found to be the principal toxicity of amrubicin monotherapy in previous phase II studies [14,15,16]. Likewise, the major adverse events in our study were hematologic toxicity, especially neutropenia and leukopenia.…”
Section: Discussionsupporting
confidence: 74%
“…Likewise, the major adverse events in our study were hematologic toxicity, especially neutropenia and leukopenia. Nevertheless, the toxicities were evaluated under third-line or later-line conditions, and no increases in Grade 3 or 4 hematologic toxicity were observed in comparison with the results reported in the above-mentioned phase II studies [14,15,16]. The incidences of severe neutropenia and leukopenia in our study were lower in the group of patients who received the 35 mg/m 2 dose than in the group treated with 40 mg/m 2 , and the clinical response of the 35 mg/m 2 group patients was not inferior to that of the 40 mg/m 2 group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phase II trials of second- or third-line AMR monotherapy for the treatment of SCLC, the response rates and the overall survival were 21–53% and 6–12 months, respectively [4,5,6,7,8,9,10,11]. In the treatment of NSCLC, the response rates of AMR monotherapy were 12–28% [11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Amrubicin and amrubicinol are inhibitors of DNA topoisomerase II, developing their cytotoxic effects by stabilizing a topoisomerase II-mediated cleavable complex. The two clinical studies of amrubicin alone for patients with previously untreated NSCLC have shown objective response rates of 28 and 18%, and median survival of 9.8 and 8.2 months [14,15]. The phase II trial in combination with platinum for previously untreated patients of extensive-stage small cell lung cancer demonstrated a favorable outcome (response rate 87.8%, MST 13.6 months) [16], but no trial of the combination with cisplatin for NSCLC has been performed.…”
Section: Introductionmentioning
confidence: 99%